What is the difference in concussion management in children as compared with adults? A systematic review. Issue 12 (28th April 2017) - Davis, Gavin A; Anderson, Vicki; Babl, Franz E; Gioia, Gerard A; Giza, Christopher C; Meehan, William; Moser, Rosemarie Scolaro; Purcell, Laura; Schatz, Philip; Schneider, Kathryn J; Takagi, Michael; Yeates, Keith Owen; et al.
Abstract : Aim: To evaluate the evidence regarding the management of sport-related concussion (SRC) in children and adolescents. The eight subquestions included the effects of age on symptoms and outcome, normal and prolonged duration, the role of computerised neuropsychological tests (CNTs), the role of rest, and strategies for return to school and return to sport (RTSp). Design: Systematic review. Data sources: MEDLINE (OVID), Embase (OVID) and PsycInfo (OVID). Eligibility criteria for selecting studies: Studies were included if they were original research on SRC in children aged 5 years to 18 years, and excluded if they were review articles, or did not focus on childhood SRC. Results: A total of 5853 articles were identified, and 134 articles met the inclusion criteria. Some articles were common to multiple subquestions. Very few studies examined SRC in young children, aged 5–12 years. Summary/conclusions: This systematic review recommends that in children: child and adolescent age-specific paradigms should be applied; child-validated symptom rating scales should be used; the widespread routine use of baseline CNT is not recommended; the expected duration of symptoms associated with SRC is less than 4 weeks; prolonged recovery be defined as symptomatic for greater than 4 weeks; a brief period of cognitive and physical rest should be followed with gradual symptom-limited physical and cognitive activity; all schools be encouraged to have a concussion policy and should offer appropriate academic accommodations and support to students recovering from SRC; and children and adolescents should not RTSp until they have successfully returned to school, however early introduction of symptom-limited physical activity is appropriate. Systematic review registration: PROSPERO 2016:CRD42016039184